APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS OF GYNECOLOGICAL DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Human-Centered Artificial Intelligence (HCAI) is an approach that creates support systems that can act as intelligent companions of experts, reflecting their thinking and decision-making process in solving real-world problems. This makes it an effective tool for improving the quality of medical services and reducing the burden on doctors. In our study, we focused on evaluating the accuracy and effectiveness of GAID in supporting the work of a gynecologist in clinical practice.